Abortion and public opinion in Great Britain: a 50-year retrospective. Issue 4 (2nd October 2018) - Clements, Ben; Field, Clive D.
Abstract: Trends in attitudes to abortion in Britain are reviewed from the perspective of opinion polls and sample surveys for the half-century since the passage of the Abortion Act 1967. The public's approach to abortion is found to have been mostly 'situationalist', conditioned by the circumstances in which abortions were to be carried out, rather than absolutist. Abortions for traumatic reasons have typically been approved from the outset but abortions for social reasons divided opinion, although they have become more acceptable over time, and very few people indeed now reject abortions in all circumstances. Results from 'non-situationalist' questions, asking about abortion in general, proved harder to interpret and were sometimes apparently contradictory or characterised by a concentration of replies in a middle ground of ambivalence, neutrality, or the avoidance of expressing strong views.